Isolation of Streptomyces strain inhibitors of toxigenic fungi. Partial characterization of their chitinolytic system - Chacón, Gustavo; Henning Vainstein, Marilene; Schrank, Augusto; Fulgueira, Cecilia (Boletín Micológico, 2001)
In the search of potencial biocontrollers for toxigenic fungi we isolated 27 soilcorne Streptomyces spp. and performed confrontation tests against toxigenic strains of Aspergillus parasiticus (aflatoxins producer), Fusarium sporotrichoides (T-2 and HT-2 toxin producer) and Fusarium graminearum (deoxynivalenol and nivalenol producer). The growth of at least one of the toxigenic fungi was inhibited by 63% of the Streptomyces isolates, 41% of the Streptomyces strains inhibited the growth of at least two tested gunfi, and 36% of the Streptomyces were effective against all three fungi. Moreover, the ability of isolates to degrade colloidal chitin was analysed and the chitinolytic complex of two of the Streptomyces strains were further characterized. Sixty six % of the Streptomyces spp. degraded colloidal chitin in the plate assays. Chitinase secretion of two isolates was assayed by colorimetric methods and by activity gels, and the degradation products from differemt substrates were analysed by thin layer chromatography.